A remark on the extension of the concept of incidence algebras to nonlocally finite partially ordered sets - Boniface I. Eke (International Journal of Mathematics and Mathematical Sciences)
An incidence algebra of a nonlocally finite partially ordered set Q is a very rare concept, perhaps nonexistent. In this note, we will attempt to construct such an algebra.